Multiple Intelligence Profiles and Creative Learning Styles among Form Four students in Selangor - Hor, Yen Yi (2012)
The study aims to obtain an overview of the multiple intelligence profile, creative learning styles, and creativity level of Form 4 students, as well as investigate the relationship and correlation between multiple intelligence profile, creativity profile, and creative learning styles of Form 4 students according to gender and subject stream in Selangor. The design of the study was a descriptive correlation study. The sample of the study was selected through random sampling method. A total of 497 Form 4 students from five schools in Selangor were selected through convenience sampling. A Multiple Intelligence Profile, Creativity Profile, and Creative Learning styles questionnaire was used for data collection. The data was analyzed using Statistical Packages for Social Sciences (SPSS) version 18. Findings of the study shows that there were significant differences in the multiple intelligence profiles, creativity profile, and creative learning styles of students according to gender and subject stream. In terms of multiple intelligence profiles, male and female students showed significant difference in their visual spatial, linguistic, musical and kinaesthetic intelligence. On the other hand, Science and Art students showed significant differences in their overall multiple intelligences profile, naturalistic, logical-math, and interpersonal intelligence. Study findings on creativity profile showed that male and female students had significant difference in their playfulness and extroversion characteristics. On the other hand, Science and Art students demonstrated significant difference in students’ overall creativity characteristics, openness, playfulness,imagination and fantasy, and extroversion characteristics. In terms of creative learning styles, visual spatial creative learning style is the only learning style that has a significant difference between male and female students. On the other hand, Science and Art students showed significant difference in their overall creative learning styles, linguistic,kinaesthetic, interpersonal, and logical math creative learning styles. In addition, study findings also indicate that there is a significant and positive relationship between multiple intelligence profile and creative learning style, as well as between creativity profile and creative learning style according to gender and subject stream. Male students were found to have a strong correlation between their linguistic intelligence and linguistic learning styles, followed by between their overall multiple intelligences with logical-math learning style and between their overall creative learning styles with linguistic intelligence whereas female respondents were found to have a strong correlation between their overall multiple intelligences with interpersonal and intrapersonal learning style. In terms of subject stream variable, respondents from the Science and Art stream were found to have the strongest correlation between their linguistic intelligence and linguistic learning style. Furthermore, study findings indicated that the strongest correlational relationship between creativity characteristics and creative learning styles among male and female students was between the overall creativity characteristics with both intrapersonal and interpersonal learning styles and followed by between the overall creative learning styles with playfulness. In terms of the subject stream variable, Science students showed highest correlation between their creative characteristics with intrapersonal learning style,followed by openness, passionate, as well as the overall creative characteristics with intrapersonal learning style. On the other hand, Art students showed the highest correlation between their overall creative characteristics with interpersonal learning style and intrapersonal learning style, and thirdly followed by between openness and interpersonal learning style. This study would be useful in providing teachers and the society an overview of the multiple intelligence profile, creativity profile, and creative learning style of Form 4 students in Selangor based on gender and subject stream. Study findings on these variables are believed to aid curriculum designers, policy makers, and teachers in the planning and implementation of curriculum and instructional strategies as well as the preparation of instructional materials that emphasised on individual differences. The outcome of the study findings can also be useful to students, where they can identify and use their strengths to succeed in their studies.